Efficacy and Safety of Topical Application of Olive Oil for Preventing Pressure Ulcers: A Systematic Review and Meta-Analysis of Randomized Controlled Trials - Hernández-Vásquez, Akram (2022)
he purpose was to identify and summarize the existing evidence on the efficacy and safety of the topical application of olive oil for preventing pressure ulcers (PUs). We included only randomized controlled trials (RCTs) involving patients at risk of developing PUs, testing the topical application of olive oil versus other products for PU prevention. We assessed the risk of bias using the RoB 2 tool, and the certainty of the evidence with GRADE. Four RCTs met the eligibility criteria. All studies were judged at a low risk of bias overall. The meta-analysis showed that the clinical efficacy of olive oil for prevention occurs by reducing the incidence of PUs (RR = 0.56, 95% CI = 0.30 to 0.79, I2 = 0%); with no differences in adverse effects, it may be associated with a shorter development time of PUs and shorter hospital stays. The certainty of the evidence assessed by the GRADE approach was moderate and low. The topical application of olive oil is effective and safe in reducing the incidence of PUs compared to other treatments. These findings could provide new insights into olive oil as a preventive and alternative treatment for PUs as it is accessible and inexpensive compared to other products.